2005
DOI: 10.1007/s00265-005-0913-y
|View full text |Cite
|
Sign up to set email alerts
|

Mating system of a Neotropical roost-making bat: the white-throated, round-eared bat, Lophostoma silvicolum (Chiroptera: Phyllostomidae)

Abstract: The vast majority of bats strongly depend on, but do not make, shelters or roosts. We investigated Lophostoma silvicolum, which roosts in active termite nests excavated by the bats themselves, to study the relationship between roost choice and mating systems. Due to the hardness of the termite nests, roost-making is probably costly in terms of time and energy for these bats. Video-observations and capture data showed that single males excavate nests. Only males in good physical condition attracted females to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 42 publications
(53 reference statements)
6
80
1
1
Order By: Relevance
“…It has been suggested that males tend to be larger than females in bat species under stronger sexual selection, or in which investing in harem defense is needed to maintain a polygynous mating system (Dechmann et al 2005;Campbell 2008). …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that males tend to be larger than females in bat species under stronger sexual selection, or in which investing in harem defense is needed to maintain a polygynous mating system (Dechmann et al 2005;Campbell 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Esta especie típicamente ocupa termiteros, y en Panamá Kalko et al (2006) estudiaron la estructura, modifi cación y disponibilidad de la pecha y determinaron que los machos excavan y mantienen cavidades en el interior de los nidos activos de termitas. El éxito reproductivo de los machos justifi ca el esfuerzo y el microclima en el nido (cálido y estable) provee un refugio adecuado para la reproducción de las hembras (Dechmann et al 2005). Por otro lado, el uso de estos nidos reduce la competencia con otras especies de murciélagos en simpatría, y reduce la carga de parásitos (Kalko et al 2006).…”
Section: Familia Noctilionidae Gray 1821unclassified
“…Such groups are usually called harems, although the female composition is often unstable or only temporarily stable (Storz et al 2000;Dechmann et al 2005). This is also known from other polygynous mammals such as ungulates (e.g., Ruckstuhl and Neuhaus 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This bat lives year-round in small groups of one adult male with a maximum of 11 females and the most recent cohort of immature offspring. The majority of the males are solitary or live in bachelor groups (Dechmann et al 2005). Solitary males excavate active termite nets and use the resulting cavity as a day roost.…”
Section: Introductionmentioning
confidence: 99%